Bill Gates Covid19 Conspiracy in Reddit Memes: A Semiotic Approach - azka saeful haq; intan siti nugraha (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2020)
Covid19 as global issue connects other social variables such as Bill Gates conspiracy issue that becomes the most predominant covid19 issue discussed globally in public (Shalini, 2020). Memes as meaningful entities exist to influence internet public in facing Bill Gates issue even without rational and empirical inquiry for some particular people that believe in them. Reddit website as easily accessible website becomes one of memes website that shares actively more numerous memes related to Bill Gates conspiracy issue than the other websites. The memes contain cultural values represented by verbal forms and visual forms to exchange belief and rational arguments.This study conducts interpretation data based on qualitative mtethod. Associating particular signifiers to Bill Gates in whole data refer to Bill Gates’ negative track record, past ideas, ambitions, and pace. Several data contain visual signifier and written signifier that support each other to acquire signified in a data such as Bill Gates in virus form who injects an old man. Signifiers reflect predominatly negative assosiations related to Bill Gates. It explicates negative connotation that exists consistently. Myths which exist represent that Bill Gates’s vaccine as a danger, Bill Gates as a mastermind behind the pandemic, and Bill Gates as an opportunist who concerns on expansion of business to reach vaccine business.